Household Dysfunction Is Associated With Bullying Behavior in 10-year-old Children: Do Socioeconomic Circumstances Matter? - Fraga, Sílvia (Journal of interpersonal violence, 2022)
This study measured the prevalence of bullying behavior in 10-year-old children and investigated the effect of the socioeconomic context on the impact of household dysfunction on bullying. We studied 5,338 members of the Portuguese Generation XXI birth cohort. Information on involvement in bullying, socioeconomic characteristics, and household dysfunction was collected by trained interviewers using structured questionnaires. Being a victim of bullying was reported by 14.4% of participants, being a bully by 1.4%, and being a bully-victim by 3.9%. Being a victim or both bully-victim, simultaneously, was more frequent among children from medium-high income families. Also, children from low-income families who reported household substance abuse, witnessed parents? intimate partner violence, and were victims of physical violence, were more frequently victims of bullying; and those who experienced family violence were more frequently involved as bully-victims. Among children from medium-high income families, all these household adversity experiences significantly increased the odds of being victim, bully, or bully-victim. Thus, although children from medium-high income families are less likely to experience adversity at home, when it happens, there is a greater effect on their behavior, suggesting that better socioeconomic circumstances do not seem to act as a protective factor.